5(x - 3) = 3(x + 2) how we will solve this question I didn't understand

Asked by shabreensayyed555 | 2nd Feb, 2022, 09:34: PM

Expert Answer:

The given question 5(x - 3) = 3(x + 2) is an equation in one variable 'x'.
 
We will solve to get a value of 'x' by doing some simplification on both sides of the equation.
5(x - 3) = 3(x + 2)
5x - 15 = 3x + 6 
5x - 15 - 3x = 3x - 3x + 6 ......  (subtracting 3x from both sides)
2x - 15 = 6
2x = 6 + 15  .........................  (adding 15 on both sides)
2x = 21
x = 21/2
 

Answered by  | 2nd Feb, 2022, 10:31: PM